The Winds in the World of Ancient Mesopotamian Civilizations - Neumann, J.
until ca. 700 B.C. Mesopotamian civilizations did not have cardinal directions (N, E, S, W) but wind-directions NW, NE, SE, SW; courtesy K. Butz.